Chambers Concise Dictionary - Edited by Davison, G. W. ; Seaton, M. A. and Simpson, J. (Cambridge Chambers, 1989)
This dictionary is an abridged version of the "Chambers English Dictionary" and is aimed at those who want an emphasis on the language of the 1980s. It contains over 121,000 references and 156,000 definitions
Keywords: English language